2018
DOI: 10.1002/jlb.1a0318-098r
|View full text |Cite
|
Sign up to set email alerts
|

JAG2 signaling induces differentiation of CD14+ monocytes into Langerhans cell histiocytosis-like cells

Abstract: Langerhans cell histiocytosis (LCH) is a MAPK pathway-driven disease characterized by the accumulation of CD1a + langerin + cells of unknown origin. We have previously reported that the Notch signaling pathway is active in LCH lesions and that the Notch ligand Jagged2 (JAG2) induces CD1a and langerin expression in monocytes in vitro. Here we show that Notch signaling induces monocytes to acquire an LCH gene signature and that Notch inhibition suppresses the LCH phenotype.In contrast, while also CD1c + dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…High serum concentrations of TGF and CSF-1 have been found in LCH patients, suggesting their contribution in the differentiation of tissue-infiltrating neoplastic LCs from hematopoietic precursors (48). Transcriptomic studies revealed a monocyte-LC signature for LCH cells driven by JAG2-mediated activation of Notch (49). We observed a hybrid phenotype of BRAF V600E LCH cells, with cDC2 markers (BDCA1 + and IRF4 + ) admixed to LC markers (CD1a, CD207, and CSF1R) indicating that a partial LC commitment of cDC2 circulating precursors might also occur.…”
Section: Discussionmentioning
confidence: 75%
“…High serum concentrations of TGF and CSF-1 have been found in LCH patients, suggesting their contribution in the differentiation of tissue-infiltrating neoplastic LCs from hematopoietic precursors (48). Transcriptomic studies revealed a monocyte-LC signature for LCH cells driven by JAG2-mediated activation of Notch (49). We observed a hybrid phenotype of BRAF V600E LCH cells, with cDC2 markers (BDCA1 + and IRF4 + ) admixed to LC markers (CD1a, CD207, and CSF1R) indicating that a partial LC commitment of cDC2 circulating precursors might also occur.…”
Section: Discussionmentioning
confidence: 75%
“…The mutation was present in all cellular subsets tested, although at much higher frequency in myeloid lineage cells (Figure 2B). While BRAF V600E has also been described in CD19 + B lymphocytes 24 and CD3 + lymphocytes 25 , this is the first description of BRAF V600E in NK cells and granulocytes.…”
Section: Resultsmentioning
confidence: 67%
“…14,15,17,31 Furthermore, a recent study showed that CD14 1 monocytes could acquire gene signature with similarities to the LCH CD1a 1 CD207 1 cell signature in the presence of Notch ligands JAG2 in vitro. 45 It remains possible that CD14 1 monocytes could differentiate rapidly into LCH CD1a 1 CD207 1 DCs once entering the lesion, or that a small population of CD14 1 DCs that present in LCH lesions may not be captured by the experiments in this study. Notably, unlike a previous report, 46 we did not detect any CD207 1 cells in peripheral blood of either LCH patients (high or low risk) or healthy controls (supplemental Figure 9).…”
Section: Discussionmentioning
confidence: 87%
“…Given the ability to differentiate into langerin 1 (CD207 1 ) cells in vitro, both CD1c 1 mDCs and CD14 1 monocytes are potential candidates to give rise to LCH CD1a 1 CD207 1 DCs. 14,15,17,31,45 To determine the differentiation pathway(s) of LCH CD1a 1 CD207 1 DCs, we first compared the gene-expression profiles of CD1a 1 CD207 1 DCs to gene signatures from human myeloid cell lineages. LCH CD1a 1 CD207 1 cells were most highly enriched with CD1c 1 mDC signature, with relatively lower enrichment with the CD14 1 monocyte signature using both CMAP and BubbleGum analysis platforms (Figure 2A-B).…”
Section: Discussionmentioning
confidence: 99%